Continuous effect of migrant crisis on smoking status among migrants - Monika Tushevska Mitkovska; Deska Dimitrievska; Marija Zdraveska; Nikola Chamurovski (European Respiratory Society, 2020)
Introduction: Acknowledging the specific problems of smoking prevalence and cessation in specific high risk populations in 2018, we have conducted a pilot research among migrants in the transitional refugee camps in Bosnia and Hercegovina, to evaluate their smoking habits, showing that migrants crisis has a negative impact on their smoking status. Objective and Method: We aimed to compare and follow the continuous effect of the crisis on the smoking habits, in order to provide data for developing a strategy that can be implemented as an continuous measure in the smoking cessation. From November untill December 2019 we interviewed a total of 368 randomly selected, migrants accommodated in the transitional camps, average length of stay of 70 days. We interwieved 333 men (90%), and 35 women (10%), age of 14-57 with the same questionnaire from the pilot study. Results: 60% were active smokers and 40% were nonsmokers.110 migrants(50%) responded that they have increased the amount of smoked cigarettes since they left they homeland, 65(20%) are smoking less cigarettes compared to the period before they left their homeland, 8(4%) have no difference in the number of smoked cigarettes, 36(16%) have started smoking since they left their homeland. None of the migrants had answered that they quit smoking since they left their homeland. Conclusion: Our data confirmed that the migration crisis has negative impact on the smoking habits of migrants. There was increase of the smoking prevalence and worsening of the smoking status true the migration crisis. We emphasize the need for organizing education and support in the process of quitting smoking for this vulnerable group.
Keywords: smoking cessation; migrants